Phthalate metabolites concentrations in amniotic fluid and maternal urine: Cumulative exposure and risk assessment. (2020) - Katsikantami, Ioanna; Tzatzarakis, Manolis N.; Alegakis, Athanasios K.; Karzi, Vasiliki; Hatzidaki, Eleftheria; Stavroulaki, Athina; Vakonaki, Elena; Xezonaki, Pelagia; Sifakis, Stavros; Rizos, Apostolos K.; Tsatsakis, Aristidis M.
Graphical abstract: Highlights: mEHP was the most detected compound in amniotic fluid and miBP in urine. The use of plastics for food storage was associated with high mEHP in urine. The use of deodorant was associated with higher urinary miBP and mnBP. A weak association was found between urinary mEHP and lower infant birth length. The daily intake of phthalates was 5.4 μg/kg bw and the hazard index 0.10. Abstract: Phthalates are used in industry as plasticizers or additives in everyday products and they have been considered as endocrine disrupting chemicals. Maternal exposure during pregnancy has been associated with neonatal exposure, preterm birth and impacts in the reproductive and respiratory systems. The aim of this study is to determine six phthalate metabolites (mono isobutyl phthalate, miBP, mono n-butyl phthalate, mnBP, mono benzyl phthalate, mBzP, mono ethylhexyl phthalate, mEHP, mono 2-ethyl-5-hydroxyhexyl phthalate, mEHHP, mono 2-ethyl-5-oxohexyl-phthalate, mEOHP) in amniotic fluid and urine from 100 pregnant women. Participants answered questionnaires for the use of plastics and cosmetics, dietary habits, health effects, pregnancy problems, health and infant development. Positive amniotic fluid samples ranged from 1% to 21% and urine from 27% to 54%. The median levels for amniotic fluid were 2.3 μg/L - 10.7 μg/L and for urine 4.9 μg/L - 46.7 μg/L. The major results include significant correlations between urinary phthalates indicating their common sources of exposure, the frequent use of deodorant was significantly associated with higher urinary miBP (p = 0.050) and mnBP (p = 0.028) and a weak inverse association was found for the use of make-up products with mBzP (p = 0.053). The frequent use of plastic food containers was significantly associated with urinary mEHP (p = 0.026), and a positive trend was noticed for mEHP in amniotic fluid (p = 0.093). An association although weak was found between urinary mEHP and lower birth length (rs = 0.396, p = 0.062). No other associations were found for infant health problems or development. The daily intake of the total phthalates was calculated 5.4 μg/kg body weight/day which corresponds to hazard index 0.10 and exposure follows the declining trend that has been observed the last decades.